ՀՀ հարկային օրենսգրքի անհրաժեշտությունն ու խնդիրները հարկային բարեփոխումների համատեքստում - Նվարդ Կարենի Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В Армении в обращение введен проект единого налогового кодекса, направленный на упрощение системы налогового законодательства, уменьшение числа составляющих ее правовых актов и обеспечение целевой на-логовой политики. Во избежание дальнейших дополнений и изменений необходимо обратить особое внимание на такие вопросы, как снижение ставки подоходного налога и порога НДС, обязательная маркировка ввозимых товаров, изменение предъявляемых требований к документам, обосновывающим расходы, соблюдение зако-нодательства ЕАЭС и так далее. The new draft unified tax code has been introduced in the Republic of Armenia, which is aimed at simplifying the system of tax legislation, reducing the quantity of its legislative acts, and to ensuring a targeted tax policy. In order to avoid further changes and additions it is required to pay a special attention to the issues such as reduction of the rate of the income tax and VAT threshold, compulsory stamping of imported goods, changes in requirements with respect to expenditure documents, compliance to the EAEU legislation, and etc.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ